Mobile-Health Reminder Management System to Monitor Hypertension Patients: A Systematic Review - Setyorini, Dwi Yoga; Fadilah, Superzeki Zaidatul; Susanti, Ika Adelia; Pradipta, Rifky Octavia (International Journal of Psychosocial Rehabilitation, 2020)
Information technology can be a medium for improving consumer health care. Since the development of industry 4.0, mobile phones have become an important tool for monitoring health interventions. The purpose of this review was to assess the effectiveness of an m-Health reminder management system for patients with hypertension. The review identified fifteen related studies following the defined inclusion and exclusion criteria, in PubMed, Science Direct, ProQuest, Sage, EBSCO, and Scopus, limited to the last 5 years, 2015 to 2020. Fifteen articles were involved in the review. Mobile phones are used as a tool for monitoring physical activity, healthy diets, education, blood pressure monitoring, symptoms and activating notifications (Reminder Management System) as a lifestyle monitoring tool every day. m-Health makes it easy for consumers to management hypertension. There should be further research related to the lifestyle monitoring of patients with hypertension.